KESTABILAN AKTIVITAS ANTIBAKTERI HASIL FERMENTASI MOLASE OLEH STREPTOMYCES RIMOSUS ATCC 33022 - Sri Handayani; Krisanti Yuwati; A. T. Karossi (Research Center for Chemistry - LIPI, 1994)
Molases and ammonium sulfate can be used as medium component to supply carbon and nitrogen respectively for production of antibacterial, through fermentation by Sirimosus ATCC 33022. During fermentation, pH, biomass and antibacterial activity against Bacillus cereus were observed. The results of this investigation indicated that the antibacterial production started after 48 hours of incubation and the maximum production was achieved after 144 hours of incubation. The antibacterial agent was extracted with n-butanol of technical grade and HCI 0.1 N and purification was carried out by recrystallization with ethanol as the solvent. The yield was 50.278 mg antibacterial agent per litre of fermentation medium. The isolated antibacterial compound possesses Amax of 266 nm whereas the oxytetracycline demonstrated maximum peak at 267nm with Eo 1.8529 x 10(4) cm(-l) M(-1). Thin layer chromatography with three eluents of the standard oxytetracycline gave Rf of 0.76; 0.64 and 0.75 while the isolated compound gave 0.76; 0.65 and 0.77 for the respective eluent. HPLC analysis on J-l-bondapak C-18 column with methanol-acetonitrile-oxalic acid 0.1 M (1 : 15 : 7) being the solvent indicated that the isolated antibacterial agent and oxytetracycline standard were eluted at 4.35 minutes. Further analysis with FTIR of both isolated antibacterial agent and oxytetracycline standard had peaks at 3400, 1650-1600, 1238 and 2916-2848 cm(-1) indicating the presence of fenol, amide, amine and methyl groups. Antimicrobial activity tests during storage at 4 °C and -12°C of the isolated compound in various HCI solutions showed that HCI 0.1 N gave the best stability.